2017
DOI: 10.1155/2017/9290454
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Study of Adsorption Kinetics of Dextromethorphan Syrup onto Activated Charcoal in Simulated Gastric and Intestinal Fluids

Abstract: Adsorption kinetics of dextromethorphan (DXM) syrup in simulated gastric and intestinal fluids onto activated charcoal (AC) were investigated in an in vitro model. The adsorption studies were performed as a function of time, initial concentration, and temperature. The quantification of DXM adsorbed onto AC was obtained from the Langmuir adsorption isotherms using HPLC. The maximum adsorption capacities (at 95% confidence limits) of AC for DXM were 111.615 [106.38; 126.85] mg in simulated intestinal environment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…have reported in vitro adsorption of dextromethorphan syrup which is an over‐the‐counter antitussive drug using activated charcoal in simulated gastric and intestinal fluids. They have showed that the use of activated charcoal might be the most effective approach for the dextromethorphan overdose treatment 5 . Nabais et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…have reported in vitro adsorption of dextromethorphan syrup which is an over‐the‐counter antitussive drug using activated charcoal in simulated gastric and intestinal fluids. They have showed that the use of activated charcoal might be the most effective approach for the dextromethorphan overdose treatment 5 . Nabais et al.…”
Section: Introductionmentioning
confidence: 99%
“…They have showed that the use of activated charcoal might be the most effective approach for the dextromethorphan overdose treatment. 5 Nabais et al have tested one of the most widely used antidepressant drugs, fluoxetine removal capacity of activated carbons, and activated carbon fibers. 6 Commercial activated carbon was also tested for metamizole sodium (dipyrone) adsorption in simulated gastric and intestinal fluids at the temperature of human body in one of our previous studies.…”
Section: Introductionmentioning
confidence: 99%